2012
DOI: 10.1111/age.12013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity and population structure of west-central Indian cattle breeds

Abstract: Evaluations of genetic diversity in domestic livestock populations are necessary to implement region-specific conservation measures. We determined the genetic diversity and evolutionary relationships among eight geographically and phenotypically diverse cattle breeds indigenous to west-central India by genotyping these animals for 22 microsatellite loci. A total of 326 alleles were detected, and the expected heterozygosity ranged from 0.614 (Kenkatha) to 0.701 (Dangi). The mean number of alleles among the catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…The moderate F ST value noted between African and Bangladeshi zebu breeds was related to their common genetic background, as the paternal origin of Ethiopian zebu is traced to the Indian subcontinent (Dadi et al, 2009). The F ST value observed here for Red Chittangong and non-descript Deshi was far lower than that reported between Ongole and Deoni zebu from India (0.117) (Metta et al, 2004) and 0.26667 for the Khillar-Kenkatha breeds of west-central India, although closer to the value (0.0126) reported for Kankrej-Malvi (Shah et al, 2012). Within populations, the genetic variability estimated for Bangladeshi zebu was higher than the reported average for Indian zebu (Shah et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…The moderate F ST value noted between African and Bangladeshi zebu breeds was related to their common genetic background, as the paternal origin of Ethiopian zebu is traced to the Indian subcontinent (Dadi et al, 2009). The F ST value observed here for Red Chittangong and non-descript Deshi was far lower than that reported between Ongole and Deoni zebu from India (0.117) (Metta et al, 2004) and 0.26667 for the Khillar-Kenkatha breeds of west-central India, although closer to the value (0.0126) reported for Kankrej-Malvi (Shah et al, 2012). Within populations, the genetic variability estimated for Bangladeshi zebu was higher than the reported average for Indian zebu (Shah et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, a total of 13932 genotypes were generated across 27 microsatellite loci in 516 cattle belonging to 10 draught type zebu breeds, 2 commercial taurine breeds and 2 crossbred populations. and comparable to that of West-Central, North and East Indian cattle (Shah et al 2012;Sharma et al 2013Sharma et al , 2015. As expected, the crossbred cattle (Jersey crossbreds and Holstein-Friesian crossbreds) exhibited a higher level of allelic diversity and heterozygosity than indigenous zebu cattle.…”
Section: Basic Diversity Measures and Hardy-weinberg Equilibriumsupporting
confidence: 72%
“…The mean F IS estimates observed in most South Indian cattle breeds were higher than those reported for East Indian (Sharma et al 2013) and most North Indian cattle with the exception of Mewati and Gaolao (Sharma et al 2015). However, the mean F IS estimates reported for West-Central Indian cattle were much higher than that of South Indian cattle (Shah et al 2012). Similarly, the mean F IS for Vechur and Ongole cattle observed in the present study was significantly lower than reported previously by Radhika et al (2018) and Sharma et al (2015) Figure SF1).…”
Section: Basic Diversity Measures and Hardy-weinberg Equilibriummentioning
confidence: 58%
See 1 more Smart Citation
“…Worldwide, cattle (Bos taurus) have been economically and culturally important farm animal species since their domestication. Many studies have assessed the diversity of cattle in Asia (Sharma et al, 2016;Nishimaki et al, 2013;Shah et al, 2013), Europe (Mateus et al, 2004;Maudet et al, 2002;Di et al, 2018), Africa (Dadi et al, 2008;Edea et al, 2015), and South America (Acosta et al, 2013;Brasil et al, 2013;Piccoli et al, 2014) and in cattle native to Korea (Suh et al, 2014). In recent years, several microsatellite studies on diversity in Chinese cattle have been published (Yang et al, 2016;Wang et al, 2015;Lou et al, 2006;Han et al, 2006;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%